2020
DOI: 10.3389/fnana.2020.00029
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Exposure to Sodium Valproate Disrupts Fasciculation of the Mesotelencephalic Dopaminergic Tract, With a Selective Reduction of Dopaminergic Output From the Ventral Tegmental Area

Abstract: Gestational exposure to valproic acid (VPA) is known to cause behavioral deficits of sociability, matching similar alterations in human autism spectrum disorder (ASD). Available data are scarce on the neuromorphological changes in VPA-exposed animals. Here, we focused on alterations of the dopaminergic system, which is implicated in motivation and reward, with relevance to social cohesion. Whole brains from 7-day-old mice born to mothers given a single injection of VPA (400 mg/kg b.wt.) on E13.5 were immunosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 96 publications
2
21
2
Order By: Relevance
“…Gestational exposure to valproic acid (VPA), a commonly used anticonvulsant, antiepileptic and mood stabilizer, results in deficits of social behavior in the offspring, modeling ASD symptoms (Dubiel and Kulesza, 2016 ; Ágota et al, 2020 ). A study compared developmental neurotoxicity when rats are exposed to VPA at E9 or E11 (Kuwagata et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…Gestational exposure to valproic acid (VPA), a commonly used anticonvulsant, antiepileptic and mood stabilizer, results in deficits of social behavior in the offspring, modeling ASD symptoms (Dubiel and Kulesza, 2016 ; Ágota et al, 2020 ). A study compared developmental neurotoxicity when rats are exposed to VPA at E9 or E11 (Kuwagata et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have revealed alterations in the dopaminergic systems of mice embryonically exposed to VPA [ 25 ]. Epidemiological and animal model studies have also suggested that perinatal alterations in 5HT, either above or below typical levels, may cause social behavioral deficits resembling ASDs [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The need for novel therapeutics remains acute as knowledge of new molecular targets has yet to be translated into clinical practice [62]. However, as new insights into the dopamine signaling anomalies in ASD stem from animal models [70][71][72][73][74][75], as well as neuroimmune theoretical frameworks [13,76,77], novel treatment approaches emerge.…”
Section: Dopamine Modulatorsmentioning
confidence: 99%
“…Given the various murine models which show a strong convergence on the midbrain dopaminergic system [70][71][72][73][74][75]93], it is tempting to speculate that this brain region is a point of junction in which diverse molecular syndromes of GPCR interactome assemble in different amounts to induce specific signaling anomalies. This assumption would fit our model which pre-dicts that the changes in the midbrain/striatal/prefrontocortical neurocircuitry should be conserved across etiologies.…”
Section: Reconceptualization Of the Dopamine Hypothesis Of Asdmentioning
confidence: 99%